2020
DOI: 10.1001/jamanetworkopen.2020.0772
|View full text |Cite|
|
Sign up to set email alerts
|

Use of Deep Learning to Predict Final Ischemic Stroke Lesions From Initial Magnetic Resonance Imaging

Abstract: IMPORTANCE Predicting infarct size and location is important for decision-making and prognosis in patients with acute stroke. OBJECTIVES To determine whether a deep learning model can predict final infarct lesions using magnetic resonance images (MRIs) acquired at initial presentation (baseline) and to compare the model with current clinical prediction methods. DESIGN, SETTING, AND PARTICIPANTS In this multicenter prognostic study, a specific type of neural network for image segmentation (U-net) was trained, v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 38 publications
5
101
0
Order By: Relevance
“…In all the external validation subjects, the presented ML model had a median Dice similarity coefficient (DSC) of 0.49 (IQR, 0.37–0.59), which was comparable to the DSC of 0.53 (IQR, 0.31–0.68) in the study by Yu et al [ 19 ]. The presented ML model had a median DSC of 0.43 (IQR, 0.20–0.52) in the SR external validation subjects and a median DSC of 0.58 (IQR, 0.55–0.67) in the UR external validation subjects.…”
Section: Resultssupporting
confidence: 74%
“…In all the external validation subjects, the presented ML model had a median Dice similarity coefficient (DSC) of 0.49 (IQR, 0.37–0.59), which was comparable to the DSC of 0.53 (IQR, 0.31–0.68) in the study by Yu et al [ 19 ]. The presented ML model had a median DSC of 0.43 (IQR, 0.20–0.52) in the SR external validation subjects and a median DSC of 0.58 (IQR, 0.55–0.67) in the UR external validation subjects.…”
Section: Resultssupporting
confidence: 74%
“…55 A multicenter study showed that an attentiongated U-Net DL algorithm with DWI and MRP as inputs could predict final infarct volume regardless of reperfusion status, with a median AUC of 0.92 (IQR, 0.87-0.96) and significant overlap with the ground truth of a FLAIR sequence obtained 3-7 days after baseline presentation (Dice score, 0.53; IQR, 0.31-0.68). 56 The e-ASPECTS software was able to predict poor clinical outcomes after thrombectomy (Spearman correlation ¼ À0.15; P ¼ .027) and was an independent predictor of poor outcome in a multivariate analysis (OR, 0.79; 95% CI, 0.63-0.99) while also demonstrating high consensus with 3 expert ASPECTS readers (ICC ¼ 0.72, 0.74, and 0.76). 57 Traditional ML techniques combining clinical data and core-penumbra mismatch ratio derived from MR imaging and MRP to determine postthrombolysis clinical outcomes performed with an AUC of 0.863 (95% CI, 0.774-0.951) for short-term (day 7) outcomes and 0.778 (95% CI, 0.668-0.888) for long-term (day 90) outcomes.…”
Section: Prognosticationmentioning
confidence: 93%
“…We used a U-Net architecture, a multi-scale network that has already shown its potential for infarct prediction tasks ( Winzeck et al, 2018 , Yu et al, 2020 ). Perfusion and diffusion MRI were used as inputs, as both modalities are complementary to evaluate the risk of infarction ( Barber et al, 1998 ).…”
Section: Methodsmentioning
confidence: 99%
“…A well-acknowledged limitation of CNNs is the large quantity of data required for their training and validation. Only a limited number of studies, with heterogeneous treatment paradigms and evaluations metrics, have evaluated CNNs for the prediction of the final stroke lesion from baseline MRI ( Winzeck et al, 2018 , Pinto et al, 2018 , Nielsen et al, 2018 , Yu et al, 2020 ) or CT ( Robben et al, 2020 ). Sample size and performance were modest ( 50 to 200 patients, Dice similarity coefficient 0.50 or lower), illustrating both the inherent difficulty of prediction tasks and scarcity of high-quality data, compared to simpler image segmentation tasks.…”
Section: Introductionmentioning
confidence: 99%